Des TIC au TOC. Contribuer à OpenStreetMap : entre commun numérique et utopie cartographique - Marina Duféal; Matthieu Noucher (Netcom)
Since the advent of geoweb, the landscape of geographic information has been constantly invested by new technical, legal and organizational arrangements on one hand, and new data producers, on the other hand. In particular, these new producers are implementing the alternatives to conventional modes of production of spatial data, from the Open movement (open source, open data, open access, open culture, open hardware, etc.) : the OpenStreetMap (OSM) project has emerged in 2004 in this context, with its community of contributors. The object of the analysis is twofold in this article : to highlight the profiles, practices, commitment values of those who constitute the hard core of the OSM community in France and to discuss the underside of this new mapping factory, that operates between utopia and digital common.